The Global Macrofinancial Model - Vitek, Francis (Washington, D.C. : International Monetary Fund, 2018)
This paper documents the theoretical structure and empirical properties of the latest version of the Global Macrofinancial Model (GFM). This dynamic stochastic general equilibrium model of the world economy, disaggregated into forty national economies, was developed to support multilaterally consistent macrofinancial policy, risk and spillover analysis. It features a range of nominal and real rigidities, extensive macrofinancial linkages, and diverse spillover transmission channels. These macrofinancial linkages encompass bank and capital market based financial intermediation, with financial accelerator mechanisms linked to the values of the housing and physical capital stocks. A variety of monetary policy analysis, fiscal policy analysis, macroprudential policy analysis, spillover analysis, and forecasting applications of the GFM are demonstrated. These include quantifying the monetary, fiscal and macroprudential policy transmission mechanisms, accounting for business cycle fluctuations, and generating relatively accurate forecasts of inflation and output growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet